PKM Teknologi RFID Internet Of Things Untuk Menuju Smart School Pada SMK N 1 Perhentian Raja - Yoyon Efendi; Syahrul Imardi; Firman Edigan; Muhammad Syaifullah; Rometdo Muzawi (LPPM STIKOM Tunas Bangsa, 2020)
Community Service Activities (PKM) are carried out at SMK N 1 Perhentian Raja through 2 methods, namely direct and online. Immediately carried out training on the installation of school CCTV which was attended by more than 20 people from students and teachers. Online through webinars which were conducted for 3 days with socialization materials for Smart School, Internet of Things and RFID. This activity also provides data packages for students and teachers in participating in webinars and online learning. This PKM activity is a series of activities from PKM STMIK Amik Riau entitled